Gender Perspective in Traditional Occupation among Hill Dalit of Kaski - Parajuli, Biswo Kallyan (Himalayan Journal of Sociology and Anthropology, 2011)
Gender perspective in traditional occupation among hill Dalit of Kaski is a study based upon a survey to explore the status of men and women and their perspectives in relation to the traditional occupation among Dalit of Kaski district. This study tries to analyse the changes observed in traditional skills of hill Dalits. Traditionally hill Dalit works as artisan, mason, carpenter, painter, builder, labour, tailor, tiller, musicians, ironworkers and shoe makers. The study describes the gender perspective in traditional occupation among hill Dalit of Kaski and presents some of the empirical evidences. The ield research has been conducted amonh 570 male and female respondents. Attempts are made to discuss on educational, occupational and economic status of men and women, occupational knowledge on traditional skill technology (TST), caste speciic occupation, TST and perception towards work of men and women, gender based difference on wage, necessity and type of training and education to the Dalit women. The inding of the study reveals that Nepali Dalit women are in dual oppression in terms of caste and in terms of gender. The study identiies that the hill Dalits are gradually shifting from their traditional occupations. DOI: http://dx.doi.org/10.3126/hjsa.v4i0.4665 Himalayan Journal of Sociology and Anthropology Vol.IV (2010) 28-48